Chronic Academic Stress Increases a Group of microRNAs in Peripheral Blood - Honda, Manami; Kuwano, Yuki; Katsuura-Kamano, Sakurako; Kamezaki, Yoshiko; Fujita, Kinuyo; Akaike, Yoko; Kano, Shizuka; Nishida, Kensei; Masuda, Kiyoshi; Rokutan, Kazuhito (PloS one, 2013)
MicroRNAs (miRNAs) play key roles in regulation of cellular processes in response to changes in environment. In this study, we examined alterations in miRNA profiles in peripheral blood from 25 male medical students two months and two days before the National Examination for Medical Practitioners. Blood obtained one month after the examination were used as baseline controls. Levels of seven miRNAs (miR-16, -20b, -26b, -29a, -126, -144 and -144*) were significantly elevated during the pre-examination period in association with significant down-regulation of their target mRNAs (WNT4, CCM2, MAK, and FGFR1 mRNAs) two days before the examination. State anxiety assessed two months before the examination was positively and negatively correlated with miR-16 and its target WNT4 mRNA levels, respectively. Fold changes in miR-16 levels from two days before to one month after the examination were inversely correlated with those in WNT4 mRNA levels over the same time points. We also confirmed the interaction between miR-16 and WNT4 3'UTR in HEK293T cells overexpressing FLAG-tagged WNT4 3'UTR and miR-16. Thus, a distinct group of miRNAs in periheral blood may participate in the integrated response to chronic academic stress in healthy young men.